Unraveling Indonesian Out-of-Field Science Teachers’ Learning at Work - Rahayu, Esti; Osman, Shuki (Bina Nusantara University, 2022)
The research aimed to show the workplace as a substantial site of learning because it allowed learning opportunities that resulted from the nature of work and social interaction with workgroups. Learning in the workplace resulted from the demand for the upskilling of employees. Although workplace learning was often considered an informal type of learning, it allowed the employees to fill the gaps between their education and their current practice through coaching and mentoring. Workplace learning happened in schools, particularly schools that hired out-of-field teachers who did not have a teaching qualification. The qualitative single case study involving teachers with more than ten years of experience teaching junior high school science in Indonesia aimed to understand better how teachers who began teaching as out-of-field teachers learned from their experiences in the workplace. In-depth interviews were employed to gain insight into their learning processes. The findings show that schools can be a conducive environment for teachers to gradually acquire skills that are increasingly central to practice through learning from professionals (both provided and requested) and colleagues (including expert teachers). As out-of-field novices lack specific knowledge of teaching this content to students in context, workplace learning enables them to change gradually.